2010
DOI: 10.1111/j.1439-0531.2008.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

Superovulatory Response of Zebu Cows Treated with pFSH in a Single Subcutaneous Injection Followed by an Additional Intramuscular Sub‐Dose 48 h Later

Abstract: Contents The aim of this study was to evaluate whether an additional intramuscular (im) injection of pFSH would increase the embryo production in zebu cows superovulated with a single subcutaneous (sc) pFSH injection. Twenty‐one Nelore cows were treated with a progesterone vaginal implant (Controlled Internal Drug Relased – CIDR B®) and injected im with 2.5 mg estradiol benzoate. Four days later, cows were assigned randomly into three groups and superovulated with pFSH. Groups A and B received single sc inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
3
6
0
Order By: Relevance
“…However, in this preliminary study, in which we used a single FSH injection for superovulation, the ovarian response was poorer than that of a traditional FSH multiple injection protocol. Similarly, in other reports (Alvarez et al 2010;Tribulo et al 2012), an additional injection of a lower dose of FSH 48 h after single administration in cows resulted in more ovulations (mean number of CL) than a single injection. Thus, a superovulation protocol in ewes using a split-single administration of HA-FSH was tested in this study.…”
Section: Discussionsupporting
confidence: 72%
“…However, in this preliminary study, in which we used a single FSH injection for superovulation, the ovarian response was poorer than that of a traditional FSH multiple injection protocol. Similarly, in other reports (Alvarez et al 2010;Tribulo et al 2012), an additional injection of a lower dose of FSH 48 h after single administration in cows resulted in more ovulations (mean number of CL) than a single injection. Thus, a superovulation protocol in ewes using a split-single administration of HA-FSH was tested in this study.…”
Section: Discussionsupporting
confidence: 72%
“…It has been reported that a single im and sc injections of FSH has the same effects with twice daily FSH treatments (1,21,35,43). In the present study, the proportion of transferable embryo yield also showed no significant difference among treatment groups.…”
Section: Discussionsupporting
confidence: 52%
“…The changes in ovarian response have been found to be related with differences in superstimulatory treatments such as total dose, duration and timing of treatment, and the use of additional hormones in the treatment protocol (38,39). Additional factors for the differences in ovarian response might be the genetic of the animal and its environment (3), dietary intake (46), breed (1,9,42), season (33), age (27,29), ovarian status at the time of the treatment (5, 18) and the effects of repeated superstimulations (30). It has been reported that application of FSH in various forms and ways other than im injection can induce superovulatory response and subcunaneous fat amount is considered to be a determinant factor in cattle (10,25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations